Social Media, Health Misinformation, and Literacy: A Narrative Review of Challenges and Solutions - Nugrahani, Marshanda Rimadita (Journal of Health Literacy and Qualitative Research, 2022)
Health misinformation on social media has become a pressing public health challenge, particularly among individuals with low digital health literacy. This study examines the relationship between digital health literacy and the spread of misinformation, analyzing systemic factors that contribute to the persistence of misleading health content. A systematic literature review was conducted using academic databases such as PubMed, Scopus, and Google Scholar, with a focus on peer-reviewed studies published in the past decade. The review identifies key demographic, social, and economic determinants influencing digital health literacy and explores the role of social media platforms in misinformation dissemination. Findings reveal that individuals with limited digital health literacy struggle to critically evaluate health-related content, making them more vulnerable to misinformation. Systemic factors, including weak regulatory oversight and social media algorithms prioritizing engagement-driven content, further facilitate the spread of misleading health information. Effective interventions, such as digital literacy education, peer-led initiatives, and collaboration between social media platforms and public health organizations, are crucial in mitigating misinformation. The study highlights the need for targeted policy reforms, improved algorithmic transparency, and community-based health education to enhance digital health literacy and misinformation resilience. Future research should focus on the long-term efficacy of digital health literacy interventions and explore AI-driven solutions for misinformation detection.